SCIENTIFIC FOUNDATIONS OF THE PROBLEM OF PREPARING PEDAGOGICAL PSYCHOLOGISTS FOR PROFESSIONAL ACTIVITY - Khalimova Malika Mirrasilovna (Journal of Applied Science and Social Science, 2026)
This scientific article comprehensively analyzes the theoretical and methodological foundations of the problem of preparing pedagogical psychologists for professional activity while substantiating the factors influencing the formation of professional competencies in modern educational systems as well as identifying the psychological and pedagogical determinants that affect the level of professional readiness and providing a scientific basis for evaluating criteria of professional preparedness in the context of contemporary educational transformations